Blackberry winter : a novel - Jio, Sarah (Plume, 2012)
"Seattle, 1933. Vera Ray kisses her three-year-old son, Daniel, good night and reluctantly leaves for work. She hates the night shift, but it's the only way she can earn enough to keep destitution at bay. In the morning--even though it's the second of May--a heavy snow is falling. Vera rushes to wake Daniel, but his bed is empty. His teddy bear lies outside in the snow. Seattle, present day. On the second of May, Seattle Herald reporter Claire Aldridge awakens to another late-season snowstorm. Assigned to cover this "blackberry winter" and its predecessor decades earlier, Claire learns of Daniel's unsolved abduction and vows to unearth the truth--only to discover that she and Vera are linked in unexpected ways"--